EXPERIMENTAL EVALUATION OF THE ANTI-ULCER ACTIVITY OF GRAPE (VITIS VINIFERA) SEED EXTRACT IN WISTAR ALBINO RATS AGAINST HYDROCHLORIC ACID â€“ ETHANOL INDUCED ULCER MODEL - Ingale, Anand M; Pinnelli, Dr. Venkata Bharatkumar; Rajendran, Dr. Vijaya (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Background: Herbal products are finding increasing demand in the treatment of Peptic ulcer, on account of their better safety and efficacy. Objectives: To evaluate the anti-ulcer activity of ethanolic extract of seeds of Vitis Vinifera in Wistar albino rats. Methods: The ethanolic extract of Vitis Vinifera was investigated for its anti-ulcer activity in rats against HCl â€“ Ethanol induced ulcer model. The antiulcer activity was assessed by determining and comparing gastric volume, pH, free and total acidity; ulcer number and its inhibition, ulcer severity and ulcer index. Results: A significant antiulcer activity was observed. The grape seed 100mg/kg group showed significant [p < 0.05] reduction in ulcer number 30.00 Â± 3.23 as compared to the control. The grape seed 200mg/kg showed significant [p < 0.05] reduction in ulcer number 27.33 Â± 2.97, free acidity 20.00 Â± 2.26, and gastric lesion18.00 Â± 2.96 as compared to the control. Conclusion: This present study indicates that Vitis vinifera seed extract has potential anti ulcer activity in the model tested. Â Keywords: Vitis vinifera, Anti-ulcer, Ethanol, Free acidity, Total acidity